Macro periodisation of competition in international women's tennis: Insights for long-term athlete development - Perri, T.; Duffield, R.; Murphy, A.; Mabon, T.; McGillivray, I.; Reid, M. (International Journal of Sports Science & Coaching, 2023)
Aims This study reports the multi-year periodised international competition engagement of elite top 100 [T100] and 250 [T250] female tennis players during their youth.